التقويم الاقتصادي لزراعة التين في محافظة اللاذقية - درويش, نضال; جحجاح, محسن; حموده, احمد (Latakia University Journal -Biological Sciences Series, 2020)
The research aims to study the economic efficiency of fig cultivation in Latakia Governorate, the study was conducted in some farms which are producing fig in Jableh, Haffa, and Lattakia city. The study calculated the average productive costs and returns, economic efficiency, per a donum of fig trees during the stage of economic fruition ( just the tenth year), period study was in 2016. The total productive costs of the fig trees cultivation per a donum have achieved 157067.75 SP/donum, the average of gross income is 420000 Sp/donum, while the net return per kilogram is 219.12 SP/donum, and the net farm income is 273975.04 SP/donum, while the net economic return is 262932.25 SP/donum. The rate of rent coefficient relative to productive costs amounted to 317.32%, and the rate of rent coefficient relative to invested capital amounted to 201.42%, while the rate of profitability coefficient relative to productive costs amounted to 263.72%, and the rate of profitability coefficient relative to invested capital amounted to 167.40%. The period of redemption of the invested capital is 0.6 year, and general economic efficiency is 2.67 . يهدف البحث إلى دراسة الكفاءة الاقتصادية لزراعة التين في محافظة اللاذقية, حيث أُجري البحث على عدد من المزارع المهتمة بإنتاج التين في مناطق جبلة والحفة واللاذقية. وتم من خلال البحث حساب متوسط التكاليف والعوائد الإنتاجية, وبعض مؤشرات الدخل المزرعي ومؤشرات الكفاءة الاقتصادية, وذلك لدونم واحد مزروع بأشجار التين خلال مرحلة الإثمار الاقتصادي ( السنة العاشرة فقط ), حيث كانت فترة الدراسة في عام 2016 . بلغت قيمة التكاليف الإنتاجية الإجمالية لدونم واحد مزروع بأشجار تين 157067.75 ل.س/دونم, وبلغ متوسط الإيراد الإجمالي السنوي 420000 ل.س/دونم, كما بلغ العائد الصافي من الكيلو غرام الواحد 219.12ل.س/كغ, وكان صافي الدخل المزرعي 273975.04 ل.س/دونم, في حين بلغ العائد الاقتصادي الصافي 262932.25 ل.س/دونم, أما معامل الريعية بالنسبة لتكاليف الإنتاج الأساسية فبلغ 317.32%, بينما بلغ معامل الريعية بالنسبة لرأس المال المستثمر201.42%, في حين بلغ معامل الربحية قياساً لتكاليف الإنتاج الأساسية 263.72%, أما معامل الربحية قياساً لرأس المال المستثمر فبلغ 167.40%, بينما كانت فترة استرداد رأس المال المستثمر 0.6سنة, والكفاءة الاقتصادية العامة 2.67.